KEBUTUHAN PANGAN POKOK UNTUK PENANGGULANGAN BENCANA DI KABUPATEN SLEMAN - Rustiawan, Asep; Mansur, Abdul Rohim (Universitas Ahmad Dahlan, 2014)
ABSTRACTBackground: Sleman district including proneness. Disasters cause suffering food insecurity, so that attempts to anticipate very necessary.The purpose of this research was to calculate how much of staple food such as rice and noodles as a source of energy required by the population especially those living in the area of Disaster Prone Areas (DPA) in Sleman in case catastrophic volcanic eruptions occur.Methods: This research was a quantitative descriptive research, calculate the amount of energy required by the population living in DPA using calculations of Recommended Daily Intake (RDI) average energy age group (kcal).The amount of energy sufficiency obtained than converted into food rice and instant noodles.The data collected was secondary data obtained from the relevant authorities such as the map of DPA, the amount and composition of the population by age and price of rice and instant noodles. Data was processed by Microsoft Excel and Nutri Survey Programs.Results and Conclusions: Recommended Dietary Intake (RDI) of resident in the area of Disaster Prone Areas (DPA) Sleman Regency were 339,964,150 kcal with the average achievement level of energy consumption is less category. If converted into staple food, it is equivalent to 49.7 tonnes of rice (Rp 374,250,000) and 2,137 boxes of instant noodles (Rp 102,624,000). Food reserves or budget must be provided for 5 days in anticipation of the needs of the population in the region when volcanic eruptions occur are as much as 248.5 tonnes of rice and 10,685 boxes of instant noodles, or equivalent to Rp 2,384,370,000. The number of staple food that has been provided by the government as much as 31 tons of rice, or 62.4% of the population requirements in a day.Keywords : Merapi, Food Disaster, Sleman District, PDA